Ionospheric‐thermospheric UV tomography: 2. Comparison with incoherent scatter radar measurements. Issue 3 (8th March 2017) - Dymond, K. F.; Nicholas, A. C.; Budzien, S. A.; Stephan, A. W.; Coker, C.; Hei, M. A.; Groves, K. M.
Abstract: The Special Sensor Ultraviolet Limb Imager (SSULI) instruments are ultraviolet limb scanning sensors that fly on the Defense Meteorological Satellite Program F16‐F19 satellites. The SSULIs cover the 80–170 nm wavelength range which contains emissions at 91 and 136 nm, which are produced by radiative recombination of the ionosphere. We invert the 91.1 nm emission tomographically using a newly developed algorithm that includes optical depth effects due to pure absorption and resonant scattering. We present the details of our approach including how the optimal altitude and along‐track sampling were determined and the newly developed approach we are using for regularizing the SSULI tomographic inversions. Finally, we conclude with validations of the SSULI inversions against Advanced Research Project Agency Long‐range Tracking and Identification Radar (ALTAIR) incoherent scatter radar measurements and demonstrate excellent agreement between the measurements. As part of this study, we include the effects of pure absorption by O2, N2, and O in the inversions and find that best agreement between the ALTAIR and SSULI measurements is obtained when only O2 and O are included, but the agreement degrades when N2 absorption is included. This suggests that the absorption cross section of N2 needs to be reinvestigated near 91.1 nm wavelengths. Key Points: UV radiances at 91.1 nm are inverted to produce 2‐D electron density fields Used nonnegative tomographic inversion code with pseudodiffusive regularization Comparison of the UV inversions to ALTAIR electron density measurements show excellent agreement